Project Management Success Factors For Sustainable Housing: A Framework - Bakar, Abu Hassan Abu; Abd Razak, Arman; Abdullah, Shardy; Awang, Aidah (2009)
Housing is the critical issue in global urbanization which have a tremendous impact on the environment – both during construction and through out their. As the key element in urban development, housing plays a vital role in attaining the goal of sustainable development.